Analysis of Dynamic Postural Stability through Y-Balance Test among Patients with Type-II Diabetes Mellitus: An Observational Study - Momina Mehmood, Farah Shaheen, Nabira Izhar, Hafiz Abdul Rehman, Afifa Ehsan, Anam Rehman, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: Different training tests are used to measure and train an individual for improvement in stationary and dynamic postural stability. Y-balance test has been utilized to test the dynamic postural stability among healthy individuals and athletes. Patients suffering from diabetes mellitus due to muscular weakness are prone to have altered dynamic postural stability. The primary objective of this study is to test the dynamic postural stability status of patients with Type-II diabetes mellitus through the Y-balance test. Methods: This cross-sectional observational investigation was conducted from June 2022 to November 2022 at Shalamar Hospital, Pakistan on 33 participants of both genders between the age group of 45-60 years. of both genders amid the age group of 45-60 years from the Diabetic Institute of Pakistan. A measuring tape was used to measure Y-balance test readings. SPSS software version 22 was used to analyze the results. Mean and standard deviation was calculated and independent and paired t-test were used to compare results. Results: Out of 33 study participants, 48.5% were male, and 51.5% were female. The findings of this study show that interlimb leg length differences were not noteworthy but both limbs had substantial results in the anterior direction (P ≤ 0.06). Furthermore, both males and females showed no interlimb differences in leg length in the posteromedial direction, however; females showed greater interlimb differences in the anterior and posterolateral direction (P ≤ 0.05). Practical Implication: Reference standards are indispensable for the accurate interpretation of the inspection results. Clinicians would use these normative numbers to institute a patient’s performance level. Since YBT enactment differs in diverse cultures, precise YBT reference standards must be recognized. Conclusions: Dynamic postural stability status of patients with Type-II diabetes mellitus through the Y-balance test showed significant differences appearing in the anterior reach distance than posterolateral and posteromedial reach distances, especially in females. Keywords: Diabetes Mellitus, Dynamic Postural Stability, Physiotherapy, Physical Therapy, Type II Diabetes Mellitus, Y-Balance Test.